The Transformation of Humanistic Values in Education in the Digital Age: An Analysis of the Role of Critical Literacy in Shaping Student Character - Dewi Mutiah; Fahmi Muhammad Ilham; Restu Banu Aji; Iwan Setiawan; Adlan Khoirul Abdi (MASI Mandiri Edukasi, 2026)
The rapid expansion of digital technology has reshaped higher education practices, particularly in how students access, process, and use academic information. However, this transformation also raises concerns regarding the weakening of humanistic values and students’ critical awareness in engaging with digital content. This study aims to examine the transformation of humanistic values in the digital learning environment and to analyze the role of critical literacy in shaping students’ character. This research is empirical in nature and applies a qualitative field research approach. Data were collected from 50 university students through observation, semi-structured interviews, and documentation of academic activities. The findings reveal that digital platforms are widely integrated into students’ learning processes, with Learning Management Systems (LMS) showing the highest usage rate at 80%, followed by academic search engines (72%) and digital journals (68%). Despite this high level of engagement, students’ critical literacy skills, particularly in evaluating source credibility and reflecting on the impact of information, remain underdeveloped. The study also identifies that humanistic values, such as academic integrity, responsibility, and mutual respect, continue to be reflected in students’ academic interactions, although they have not yet been fully internalized. These findings suggest that effective integration of digital technology must be accompanied by strengthening critical literacy and reinforcing humanistic values to foster students who are reflective, ethical, and responsible in navigating digital information.